2018
DOI: 10.3390/rs10020336
|View full text |Cite
|
Sign up to set email alerts
|

Using Satellite Error Modeling to Improve GPM-Level 3 Rainfall Estimates over the Central Amazon Region

Abstract: Abstract:This study aims to assess the characteristics and uncertainty of Integrated Multisatellite Retrievals for Global Precipitation Measurement (GPM) (IMERG) Level 3 rainfall estimates and to improve those estimates using an error model over the central Amazon region. The S-band Amazon Protection National System (SIPAM) radar is used as reference and the Precipitation Uncertainties for Satellite Hydrology (PUSH) framework is adopted to characterize uncertainties associated with the satellite precipitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…We used the Roebber performance diagram (known as a performance diagram) to represent the geometric relationship between these four quality measures. Many researchers have utilized this diagram to elaborate the performance of remotely sensed precipitation estimates in different regions, such as Pakistan [11], Egypt [2], and Brazil [58,59]. In a performance diagram, if the values of POD, SR, CSI, and BIAS for an SPP are closer to unity, then the performance of that SPP is considered as reliable.…”
Section: Performance Of Precipitation Products At Daily Scalementioning
confidence: 99%
“…We used the Roebber performance diagram (known as a performance diagram) to represent the geometric relationship between these four quality measures. Many researchers have utilized this diagram to elaborate the performance of remotely sensed precipitation estimates in different regions, such as Pakistan [11], Egypt [2], and Brazil [58,59]. In a performance diagram, if the values of POD, SR, CSI, and BIAS for an SPP are closer to unity, then the performance of that SPP is considered as reliable.…”
Section: Performance Of Precipitation Products At Daily Scalementioning
confidence: 99%
“…Numerical models can provide spatial precipitation estimates with physical bases but require large computational resources and have large uncertainties associated with parameters [12,13]. Satellite sensors can detect precipitation information globally and can be applied to high mountains and deserts, but satellite data poorly represent variability in local areas and complex topographical regions due to their low resolutions and deficiencies in retrieval algorithms [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, error modeling is vital for improving the use of satellite-based precipitation product (GPM IMERG Precipitation estimates) in precipitation-sensitive applications such as hydrological modeling [40]. The first step to error modeling is to recognize the physical error factors and then evaluate the related error magnitudes.…”
Section: Introductionmentioning
confidence: 99%
“…The first step to error modeling is to recognize the physical error factors and then evaluate the related error magnitudes. Research on error analysis of the satellite precipitation product has been reported in several past studies, which considered the dependence on precipitation rates and types, as well as surface conditions like soil moisture and land cover [40,41]. A multidimensional satellite rainfall error model (SREM2D) developed by Hossain and Anagnostou [42] has been used in several error modeling studies of satellite rainfall products [43][44][45].…”
Section: Introductionmentioning
confidence: 99%